Reading Strategies Used By the Students of English Language Education Study Program - Pratiwi, Irma; Regina, Regina; Wardah, Wardah; Susilawati, Endang; Sumarni, Sumarni (Acitya: Journal of Teaching and Education, 2024)
The purpose of this research is to investigate the reading strategies used by the sixth-semester students of English Language Education Study Program who have the highest grade in reading subjects. There were 37 students who participated in this research. The data were obtained through the Survey of Reading Strategies (SORS) questionnaires developed by Mokhtari and Sheorey (2002) and interviews with 10 students. The data were analyzed through descriptive statistics and qualitative analysis. The result revealed that students frequently used three categories of reading strategies: global reading strategies, problem-solving strategies, and support strategies. The students also used skimming, scanning and mind mapping strategies. Then, the most frequently used reading strategies were problem-solving strategies, followed by global reading strategies and support strategies. In conclusion, the students used various reading strategies to comprehend readings well.